Reactivating the dynamism in Mercosur: A monetary approach (2020)
Considering the monetary approach, this article analyzes the feasibility of creating a new currency in the Southern Common Market (MERCOSUR) as an option to recover the dynamism observed in the previous decade. The hypothesis suggests that the creation of a new currency is desirable if it is possible to increase the growth rate of real gross domestic product (GDP) and to reduce price volatility. Empirical evidence suggests that the alternative of creating and implementing a new currency in the bloc is desirable and highly feasible due to the positive correlations observed among their countries’ business cycles and domestic currency depreciation rates, as along with the possibility of creating a central bank responsible for the common monetary policy with low inflationary bias.